Active aging in the countryside: Space, place and the performance of leisure–work lifestyles in contemporary rural China. Issue 6 (20th January 2021) - Chen, Ningning; Chen, Jingfu; Ko, Pei‐Chun
Abstract: This paper explores the performance of active aging by Chinese rural elders amidst rapid rural restructuring. Drawing on a study of combined leisure–work lifestyles of elderly males in rural Wenzhou, southeast China, it highlights the significance of space and place in forming and shaping active aging in the countryside. The wider rural transformation prompted by industrialisation and modernisation provides opportunities for them to (re)make a temple leisure space and an elderly porter centre in/through which they reconfigure everyday practices and aged identities as 'modern subjects' and 'good parents.' Such reconfiguration is simultaneously shaped by place‐based norms such as 'living a self‐sufficient later life.' It is also found that their experiences and practices of active aging are continuously mediated in time‐spaces. This is demonstrated by the influence of spatial openness and proximity and the tempo‐spatial negotiation of past experiences and differences during the performance of active aging. This paper advances a geographical approach to exploring active aging in the countryside and enriches our understanding of active aging in contemporary (rural) China.